Students Attitude for Blended Learning at Higher Education Level - Kumar, Kalakoti Uday; Hafeez, Qudsia; Sujatha, Busi (Indian Journal of Educational Technology, 2025)
Education has leapt over from the conventional mode to the modern way of teaching with the accessibility of various online platforms. A hybrid instruction model called Blended Learning, conglomerates the strengths of each conventional and online mode of learning experiences. This study explores to what extent university students have an attitude towards the blended learning approach with the objectives laid to investigate and compare the attitude of undergraduate and postgraduate students belonging to two science and two non-science streams their gender, and undergraduate and postgraduate education level. The paper analyses the result of a survey conducted on 160 students randomly selected through stratified random sampling comprising 40 students from each of the four departments of Osmania University, including 20 undergraduates and 20 postgraduates, equally representing 20 males and 20 females. The data collected through an opinionnaire on four different aspects of the blended learning model, i.e. BL environment, BL structures, BL implementation, and BL assessment and evaluation; on a 5-point Likert scale showed significant differences exist among different streams, gender, and educational level of students towards blended learning method.